ANALISIS RETURN ON INVESTMENTPADA USAHA PETERNAKAN SAPI PERAH PT. SARI INDAH KECAMATAN PEKALONGAN BARAT KOTA PEKALONGAN - Ruth Dameria Haloho (Universitas Quality, 2018)
This study aims to determine the feasibility of dairy farming business seen from its financial aspects and to find out how much profit gained from the overall investment invested. This research was carried out on the dairy farming business at PT Sari Indah, West Pekalongan Subdistrict, Pekalongan City. The research method used is the case study method. The selection of research locations with consideration of PT Sari Indah's dairy farming business is a profitable business because it is able to carry out livestock farming independently, and produce milk with good quality. The data analysis in this study was used, namely: Return On Investment (ROI), the results showed that the ROI value was 35.89%. The conclusion of this study is the dairy farming business of PT. Sari Indah was declared financially feasible because it was able to generate a return on investment invested, and the revenue received was greater than